PENYEBARLUASAN HASIL-HASIL RISET DI JURNAL ILMIAH BIDANG GEOLOGI KELAUTAN INDONESIA: PENYELIDIKAN KECEPATAN PUBLIKASI - Himawanto Himawanto (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2019)
The publication process of National Journal of Marine Geology from the submission to the approval needs to be efficient to speed up the science transfer and new bibliometric indicators in Indonesia. This study aimed to determine the editing speed in Jurnal Geologi Kelautan (Journal of Marine Geology (JGK) and Bulletin of the Marine Geology (BMG) years 2009-2017. The data consisted of 219 articles from JGK and BMG online; recorded publications history, titles, authors, institutions, citations, and pages numbers. Straight counting method was applied to authors and their institutions. Gender analysis was also applied to identify the authors’ sex. Publication history was analyzed by using editing speed norm. Pearson correlation test (p 0.05) was utilized by using IBM SPSS. The editing duration of the two journals was 199.17 days on average. In this context, BMG was considered more efficient. Statistically, citation and editing speed had significant correlation (r = -0.147, p = 0.030). Efficient editing duration performed by collaborative and female writers. Based on the main contributors, the most efficient editor was 129 days. Not only is it useful for journal quality and publication speed, efficient editing duration will increase the authors’ trust toward JGK and BMG. Future researches should be conducted on other national journals in similar fields to provide further analysis or to compare the findings. Keywords: editing speed, publication efficiency, journal quality, bibliometric